Forging reading comprehension: proposed framework for reciprocal teaching in inquiry-based reading classrooms / Ting Pick Dew, Suyansah Swanto and Vincent Pang - Ting, Pick Dew; Swanto, Suyansah; Pang, Vincent (Akademi Pengajian Bahasa, 2012)
Reciprocal Teaching (RT) is a research-based scaffolded instructional approach that disseminates a fusion of metacognitive reading strategies and collaboration within small groups of students to enhance the construction of understanding and comprehension. The modelling and application of these four reading strategies in RT; predicting, clarifying, questioning and summarizing, allow the teacher and learners to scaffold and construct meaning in a social setting, thus establish a valid meaning transaction between the reader and the text. The adequate development of these strategies is pivotal as they rectify reading difficulties by enhancing readers’ textual understanding. However, little is known about the utilization of these strategies in the inquiry-based reading classrooms. In supporting teachers’ lesson planning practices, this paper aims at proposing the integration of the RT strategies into the five phases of the 5E model. Detailed identification and description on the key reading activities based on an analysis of existing literature are highlighted. Besides offering an overview of a teaching technique that might motivate struggling readers to begin to take interest in reading through the exposure of the suggested strategies, this conceptual paper might increase teachers’ awareness of the learners’ needs and understanding on the reading purposes and strategies, thus might bring about a change in the way reading comprehension is taught in classrooms.